Estimating time to completion: Uncertain processing times in games - Iqbal A. (2023)
In this article we propose a method that enables computer programmers to generate an estimate of the time remaining in tasks that have uncertain or theoretically unpredictable processing times. The method uses the real-time mean given the time presently elapsed and the number of task components completed thus far in order to predict or estimate the amount of time remaining for the overall task. Experimental results based on a board game task in two categories suggest that the estimate can be considered reliable (i.e. within a 10% margin of error) not very long after the task has begun; in general, after approximately just 20% of it has been completed. The estimated time to completion is particularly meaningful to end-users who are otherwise just left waiting, or having to leave and return many times to check if the task has completed. The method, in principle, can be applied also to different tasks with uncertain processing times, game-related or otherwise. 2011 IEEE.